PENGARUH KUALITAS PELAYANAN JASA BENGKEL DAN PROMOSI BENGKEL TERHADAP CITRA PERUSAHAAN PADA AHASS PT. TELAGA MESTIKA MAS - Asih, Novi; Sabur, Ambuy; Ramdani, Heni Cahya (Journal of Business Education and Social, 2022)
This research was conducted at AHASS PT. Telaga Mestika Mas. This study aims to determine how much influence the service quality of workshops and workshop promotion has on corporate image at AHASS PT. Telaga Mestika Mas. This study uses a quantitative description. Data analysis using multiple linear regression, t test and f test. Data collection techniques using a questionnaire. With a population of 200 people, the sampling technique was determined, namely purposive sampling, while the sample obtained was 67 people, namely customers who came directly to the workshop. From the results of the research on the variable quality of service workshops, the value of tcount > ttable (7.002 > 1.998) is obtained. it can be concluded that the service quality of the repair shop has an effect on the company's image at the AHASS PT. Telaga Mestika Mas while workshop promotion on corporate image is tcount < ttable (1.537 <1.998) so it can be concluded that workshop promotion has no effect on corporate image at AHASS PT. Telaga Mestika Mas.